Analysis of Risk Factors for Postoperative Lower Extremity Deep Venous Thrombosis and its Treatment and Nursing - Huayun Liu; Yunhua Peng (Emergency Medicine International)
Objective. To explore the risk factors of lower extremity deep venous thrombosis (LEDVT) after surgery and discuss the treatment and nursing countermeasures. Methods. A retrospective analysis was conducted on 268 surgical patients admitted between July to December 2021. The factors associated with LEDVT were analyzed using the Logistic regression model. Further, LEDVT patients were assigned to a research group treated with targeted nursing to prevent LEDVT and a control group that used routine care. Coagulation function and inflammatory cytokines before and after nursing intervention were compared between groups. The assessment of patients’ mobility employed the lower limb motor function part of the Fugel–Meyer Assessment (FMA), Harris Hip Score (HHS), and Barthel index (BI), and their psychological status was evaluated using the Kolcaba’s General Comfort Questionnaire (GCQ) and Self-rating Anxiety/Depression Scale (SAS/SDS). Finally, patient satisfaction with the treatment service was investigated. Results. Logistic regression analysis showed that hypertension, limb paralysis, central venous catheterization of lower limbs, and bedridden time affect postoperative LEDVT in an independent way (P<0.05). After the intervention, the coagulation function and inflammatory reaction were improved in both groups, with more significant improvement in the research group (P<0.05). The research group also showed higher FMA, Harris, GCQ, and BI scores while lower SAS and SDS scores than the control group postnursing intervention (P<0.05). Finally, a higher satisfaction rate was identified in the research group as compared to the control group (P<0.05). Conclusion. Hypertension, limb paralysis, CVC of lower limbs, and bedridden time are all independent risk factors for LEDVT after surgery. The implementation of targeted nursing strategies for the above factors can effectively alleviate the hypercoagulable state of patients after operation, reduce inflammatory responses, and improve patient comfort, which is of great significance for preventing the occurrence of LEDVT.